2022
DOI: 10.3390/healthcare10060993
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Thrombophilia in the Era of COVID-19

Abstract: Thrombophilia, also called hypercoagulability or prothrombotic condition, usually reflects a certain imbalance that occurs either in the coagulation cascade or in the anticoagulation/fibrinolytic system. A similar imbalance may be induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Thrombotic complications are associated with multiorgan failure and increased mortality. In this context, activation of coagulation and thrombocytopenia appeared as prognostic markers in COVID-19. Our work provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…For example, the ROADMAP-CAD study is a prospective study that seeks to evaluate the utility of measuring hypercoagulability biomarkers to better diagnose severe coronary artery disease. This research by Gerotziafas et al showed promising results indicating that hypercoagulability assessment could be proposed to screen patients with severe CAD [76][77][78]-Table 3. • the anticardiolipin and anti-beta-2 glycoprotein-1 antibodies (IgG and IgM isotypes) and lupus anticoagulant;…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ROADMAP-CAD study is a prospective study that seeks to evaluate the utility of measuring hypercoagulability biomarkers to better diagnose severe coronary artery disease. This research by Gerotziafas et al showed promising results indicating that hypercoagulability assessment could be proposed to screen patients with severe CAD [76][77][78]-Table 3. • the anticardiolipin and anti-beta-2 glycoprotein-1 antibodies (IgG and IgM isotypes) and lupus anticoagulant;…”
Section: Discussionmentioning
confidence: 99%
“…Protein S deficiency is an inherited thrombophilia caused by reduced activity or impaired function of protein S, a glycoprotein with anticoagulant properties. Patients with protein S deficiency have a high risk of recurrence of venous thromboembolism (VTE), with an annual incidence of recurrence after the first event of 8.4% [ 1 ]. Thrombophilia can also be acquired, as it is in the setting of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors demonstrated evidence that hereditary thrombophilia is a risk for severe COVID-19 and a marker of poor prognosis. Thus, testing for hereditary and congenital thrombophilia may benefit patients with early diagnosis and prevention of thromboembolism [ 69 , 70 ].…”
Section: Pregnancy Thrombophilia and Covid-19mentioning
confidence: 99%